Perbedaan Lama Lepas Tali Pusat Pada Bayi Baru Lahir yang Memakai Benang Dan Yang Umbilical Cord Clamp - Zaini S, Hanifa; Afrianda, Anjeli (Jurnal Medisains Kesehatan, 2024)
In babies, the length of time for umbilical cord removal varies greatly, namely within 3 days, 5 days, 7 days. During the healing process, the umbilical cord can be said to fall off quickly if the length of time for it to fall off is less than 5 days. There are several tools used to tie the umbilical cord, namely using an umbilical cord clamp and using umbilical cord thread. This research aims to determine the difference in length of umbilical cord removal in newborns who use threads and those who use umbilical cord clamps at BPM Agustinar, Amd. Keb Lempur Tengah in 2023. This research is a pre-experimental type of research with a post-test only design, with divided into two groups, namely the group with thread and the group with umbilical cord clamp, which was carried out at BPM Agustinar, Amd. Keb in March-April 2023. The research population was all newborn babies at BPM Agustinar, Central Lempur starting from the start of the research until the sample was sufficient. The number of samples in this study was 16 respondents. Data analysis used the Independent T-Test. In the research results, the average length of umbilical cord removal for babies who used umbilical cord clamps was 6.38, while the average value for newborns who used umbilical cord clamps was 8.13. The results of the Independent T-Test statistical test showed a p-value of 0.033 (p<0.05).  From the research results, it was concluded that there was a difference in the length of time the umbilical cord was removed for newborns who used umbilical cord thread with an umbilical cord clamp.  It is hoped that the baby's mother will always keep the umbilical cord clean and dry, so that the process of drying the umbilical cord is faster.